Dynamics for the agroecological transition (DyTAEL) in Fatick, Senegal. Analysis of the level of agro-ecological transition, profitability, levers and obstacles for players in the school canteen goat milk value chain - Ba, Koki; Fall, Modou Gueye; Diene, Rokhaya; Ndour, Maimouna; Cesaro, Jean Daniel; Camara, Astou Diao (2024)
In Senegal, food insecurity is a major challenge to children's education, especially in regions like Fatick. To address this, school canteens have been introduced in over 11% of elementary schools, providing children with two meals a day made from local products like millet and milk. This initiative not only supports children's education but also promotes local agriculture and shortens supply chains, contributing to a circular economy. The CGIAR Agroecology Initiative (IAE) is supporting this transition by promoting sustainable business models that align with agroecology principles in Fatick with Fatick DYTAEL. The study aims to assess the level of agro-ecological practices among stakeholders in the milk value chain that supplies school canteens and to evaluate the challenges and opportunities within these local value chains. This includes a cost/benefit analysis and a SWOT analysis for each stakeholder. The goal is to provide evidence to help design business models that support the use of local, sustainable products in school canteens, enhancing food security and sustainability.